Student Engagement: Examining Flow Theory in Online and In-person Spanish Language Learning Environments - Osuman, Fati (Université d'Ottawa | University of Ottawa, 2024)
The COVID-19 pandemic forced learning institutions to adopt a mix of online, hybrid and in-person classes. Within this context, there is a pressing need to interrogate the role of student engagement and learning outcomes under the lens of these emerging learning environments (Acosta-Gonzaga & Ruiz-Ledesma, 2022). Research on student engagement in the classroom is not new – it has been widely investigated in in-person classes; by contrast, there is currently thin literature on engagement in online classes leading to some practical but critical policy questions emerging within the scholarly discourse. In line with this need, the study aimed to investigate the impact of the Learning Environment (In-person vs. Online) on Spanish students' Oral Task and Class Engagement through Flow Theory (Csikszentmihalyi, 1990). By synthesizing existing knowledge and mapping out new pathways within the engagement discourse, it also explored whether learner proficiency levels influenced engagement (i.e. flow) in the two learning settings. Through this comprehensive investigation, the study utilized the think-aloud technique (Willis, 2005; Ericsson & Simon, 1993) to validate the student engagement questionnaire. The current study addressed key research questions, including whether Spanish students experience flow in Oral Tasks. If so, to what extent do online and in-person students differ in their oral task flow? Are there differences in the proportion of class time spent in flow state between online and in-person students? Is there a relationship between the level of proficiency and student engagement level? If so, is the relationship similar for both conditions (in-person vs. online)? What are teachers’ perceptions concerning the degree of student engagement and learning in the two instructional environments? Participants involved 87 Spanish undergraduate students, 10 Spanish course instructors and seven think-aloud informants. The results suggest that in-person and online learners did not differ in their flow on the Oral task. It also revealed that in-person learners experienced a significantly longer flow state during Spanish class time than online learners. However, there is a caveat to this finding since the results also suggested that online and in-person learning environments have different flow-inducing and inhibiting factors that need to be mediated to enhance engagement in each setting. On the other hand, though initial results showed no direct impact of proficiency on flow, further analysis indicated that low proficiency learners in online classes are at a slight disadvantage in flow experiences compared to low and high proficiency students in in-person classes. Finally, instructors perceived that the in-person environment engendered more avenues for engaged learning than the online environment. The results have immediate pedagogical policy imperatives within the axis of tasks and course content design. This may benefit classroom stakeholders in designing tasks that induce optimal learning experiences for in-person and online students.
Keywords: Student engagment; Spanish; Think-aloud; Validity